Application of Evapotranspiration Models for Al-Ramadi Irrigation Project, Al-Anbar, Iraq - waheeb, mohammed; Mustafa, ayad; Al-Somaydaii, Jumaa (Iraqi Journal of Civil Engineering, 2023)
Since evapotranspiration typically makes up the largest portion of the terrestrial water cycle, it is one of the most crucial factors in determining how much water is available. This study evaluated four models (Penman-FAO-24(PF), Penman-Monteith -FAO-56(PM), Penman-Kimberly(PK), and Jensen-Haise (JH)) utilized frequently to calculate monthly reference crop evapotranspiration (ET_0) values for Ramadi irrigation project (fourth stage). The statistical indicators considered were the root mean square error (RMSE), Mean Absolute Error (MAE), Relative Error (RE), Correlation Coefficient (R^2) and mean bias error (MBE), models were used to estimate evapotranspiration, and by calculating evapotranspiration for Al-Ramadi city according to the climate data available to us, The (PF) model had the lowest MBE = 0.02945, greatest RMSE = 29.369, and highest R = 0.9641 values among the four models, demonstrating that it is the best. The JH model, which achieved the highest values of MBE = 0.00978 and RSME = 58.509, was the least accurate of the models.. The study’s conclusions may be useful to farmers, decision-makers, and local water organizations in assessing irrigation water requirements, planning, and effective use of water resources.